Co-producing research study recruitment strategies with and for children and young people for paediatric chronic pain studies - Ghio, Daniela; Lunt, Laura E.; Bridges, Angharad; Gahr, Lydia; Hood, Anna M. (Frontiers in Pain Research, 2024)
IntroductionChildren and young people experiencing chronic pain are at greater risk of inequitable and poor-quality pain management, which has implications for future management of pain in adulthood. Most chronic pain research is conducted with adults who are more likely to be middle-class, white and monocultured. Inclusive and diverse recruitment practices in paediatric pain research can be an area in which we can address this imbalance of representation. The aim of this current work was to explore these practices and to co-produce recommendations regarding recruitment strategies for paediatric pain research.MethodsThe research team worked with Your Rheum, a United Kingdom young person's advisory group (ages 11–24 years) and diagnosed with rheumatic condition(s), the opportunity to input into rheumatology research. At a virtual Your Rheum meeting, eight young people (female = 7, male = 1, age range 12–24) took part in group discussions, sharing their experiences of taking part in research and their decision process. Online tools, including Mentimeter and Miro, were used to aid conversations and share ideas.ResultsMost young people had experience of taking part in research as a study participant (n = 5). Recommendations synthesised included increased awareness of research in general. The young people discussed being open to hearing about research opportunities; they reflected that they are rarely exposed to these invitations or hear about current research. The clinic environment was highlighted as a “good and trustworthy” recruitment area – being approached by a member of the research team was considered ideal, even if it was someone they had not met previously. Many young people recalled little discussions of research at their clinical appointments. Deciding to participate in research included the following considerations: benefit/impact; connecting with others; research topic; which is then balanced against convenience, and reimbursement. The young people felt that taking part in research was empowering and helped them take ownership of their pain management.ConclusionIt is essential to understand the perspectives of potential study participants, to plan successful recruitment strategies. Ensuring we consider these factors when designing our studies and recruitment strategies is beneficial to all involved. Co-produced recruitment strategies would aid inclusive (and increased) research participation.